3D-ordered carbon materials by melt-shear organization for tailor-made hybrid core–shell polymer particle architectures. Issue 18 (18th November 2015) - Vowinkel, S.; Schäfer, C. G.; Cherkashinin, G.; Fasel, C.; Roth, F.; Liu, N.; Dietz, C.; Ionescu, E.; Gallei, M.
Abstract : The melt-shear organization technique for tailor-made polystyrene- co -polyacrylonitrile (PSAN) shell and silica core particles is investigated yielding easy-scalable carbonaceous porous films after etching and appropriate thermal treatment. Abstract : The melt-shear organization technique for tailor-made polystyrene- co -polyacrylonitrile (PSAN) shell and silica core particles is investigated yielding easy-scalable carbonaceous porous films after etching and appropriate thermal treatment. Monodisperse silica core particles are surface modified and transduced to a seeded emulsion polymerization for the preparation of processable well-defined core–shell PSAN particles. Melt-shear organization for particle alignment into a colloidal crystal structure is applied prior to the thermally induced crosslinking of the PSAN shell material, followed by etching and carbonization of the porous polymeric opal film. It is shown that polymer processing and applied thermal treatment protocols are crucial and capable of maintaining the pristine particle order in the free-standing carbonaceous films. The obtained films reveal hexagonally aligned pores as part of a conductive carbonaceous matrix. Conductivity and adjustable porosity are evidenced by conductive atomic force microscopy (C-AFM) and scanning electron microscopy (SEM) measurements, respectively. The herein developed melt-shear organization technique for a novel polymer-based carbonaceous particle precursor material is shown to be a potential platform for the preparation of scalable conductive materials. The route described here will be feasible for the preparation of doped and tailor-made conductive materials with a wide range of applications in the fields of electrodes, batteries, as well as sensing and photonic band gap materials.